Efforts to Improve the Quality of Learning of PKN Unity and Unity Material in Diversity Through Team Game Tournament (TGT) Methods in Students of Grade IV C SDN Perigi 01 Years of Lessons 2019/2020 - Nawiyah Nawiyah (Green Publisher Indonesia, 2021)
The low quality of PKn learning in students of grades IV-C at SDN Pondok Kacang Timur 03 years of lessons 2019/2020 memotiti researchers look for solutions how efforts in improving the quality of learning PKn through the Team Game Tournament (TGT) method. After the study was found 1) Student test results in cycle I meeting 1 obtained an average of 55.42 student test results with a completion percentage of 25%, cycle I meeting 2 obtained an average of student test results 63.33 with a completion percentage of 38%, cycle II meeting 1 obtained an average of student test results 72.50 with a percentage completion of 54%, cycle II meeting 2 obtained the average student test results 85.83 with a completion percentage of 100%, Showed significant improvement in performance. 2) The application of cooperative learning through TGT can improve the quality of students' civic education learning outcomes. The average grade of student test results each cycle increases. In cycle I meeting 1 obtained an average of student test results 55.42 with a percentage completion of 25%, cycle I meeting 2 obtained an average of student test results 63.33 with a percentage completion of 38%, cycle II meeting 1 obtained an average of student test results 72.50 with a completion percentage of 54%, cycle II meeting 2 obtained an average of student test results 85.83 with a completion percentage of 100%, Showed significant improvement in performance. The advice that can be given from the results of this class action research is 1) The application of a learning model with the Type team games tournament as one of the alternative learning models for teachers that can improve the quality of civic education learning. 2) Tournament games in the TGT learning model, should be designed in such a way that students are more interested and can improve the quality in students who can ultimately improve their achievements.